Early Sexual Debut and HIV Infection among Men Who Have Sex with Men in Shenzhen, China. (28th November 2016) - Xu, Ruiwei; Dai, Wenjie; Zhao, Guanglu; Tu, Dan; Yang, Lin; Wang, Feng; Cai, Yumao; Lan, Lina; Tan, Hongzhuan; Liu, Aizhong; Feng, Tiejian; Kaminga, Atipatsa C.
Abstract : Studies investigating the association between early sexual debut and human immunodeficiency virus (HIV) infection have mainly focused on Africans or females but rarely on men who have sex with men (MSM) in China. This study, therefore, mainly aimed at exploring the association between early sexual debut and HIV infection among MSM in Shenzhen, China. A total of 533 MSM were enrolled in this study using a convenience sampling method. Information about sociodemographic characteristics and risky sexual behaviors was collected. It was found that the prevalence of HIV infection was 24.2% among this study population and 66.4% of the MSM reported having had vaginal sexual intercourse with females. The mean ages at first vaginal sexual intercourse, first anal sexual intercourse, and first sexual intercourse were 21.38, 22.43, and 19.87 years, respectively. Multivariable logistic regression analyses showed that the MSM who experienced early anal sexual debut were more likely to be infected with HIV than those who did not. The results indicate that HIV infection is quite prevalent among MSM in Shenzhen. Early and efficient intervention strategies should be taken, and the MSM experiencing early anal sexual debut should be given special attention.